From here: Anna Maria Guasch and Visual Studies (REVISTA NODO, 2024)
This text starts from the concept “place of enunciation” to explore the various sites of enunciation from which Anna Maria Guasch has spoken about Visual Studies. In the first instance, the article addresses Guasch's work from the point of view of translation, providing an overview of his text “Visual Studies: A State of the Question” through the prism of an expanded translation exercise. Secondly, Guasch's work is analyzed from the point of view of archaeo-cartography, addressing his text “Twelve Rules for a New Academy” as an example of his ability to produce coordinates to navigate the discourse of Visual Studies. Finally, this text approaches Guasch's work from a site of enunciation marked by genealogy in its Foucauldian meaning. This section analyzes two recent texts that exemplify this author's work from a genealogical perspective.
Keywords: Anna Maria Guasch; Archaeology; Visual Studies; Genealogy; Image; Visuality